2018
DOI: 10.1016/j.envpol.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating microplastic trophic transfer in marine top predators

Abstract: Microplastics are highly bioavailable to marine organisms, either through direct ingestion, or indirectly by trophic transfer from contaminated prey. The latter has been observed for low-trophic level organisms in laboratory conditions, yet empirical evidence in high trophic-level taxa is lacking. In natura studies face difficulties when dealing with contamination and differentiating between directly and indirectly ingested microplastics. The ethical constraints of subjecting large organisms, such as marine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
279
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 754 publications
(346 citation statements)
references
References 49 publications
12
279
1
10
Order By: Relevance
“…The polymer make‐up of marine plastic debris may aid in identifying possible sources, degradation, fate and reasons for ingestion (Jung et al, ; Nelms et al, ). The polymers identified through FT‐IR analysis reflect the recently reported polymer diversity globally described for microplastics (Gago et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer make‐up of marine plastic debris may aid in identifying possible sources, degradation, fate and reasons for ingestion (Jung et al, ; Nelms et al, ). The polymers identified through FT‐IR analysis reflect the recently reported polymer diversity globally described for microplastics (Gago et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have shown trophic transfer of microplastics between invertebrates and within planktonic food webs (Dawson et al, ; Farrell & Nelson, ; Macali et al, ; Setälä et al, ). In addition, a recent study by Nelms et al () on grey seals ( Halichoerus grypus ) and wild‐caught Atlantic mackerel ( Scomber scombrus ) suggested that trophic transfer represents an indirect but potentially major pathway for any species whose feeding ecology involves the consumption of whole prey.…”
Section: Discussionmentioning
confidence: 99%
“…Once in food webs, plastic particles may be retained through transfers through multiple pathways (Windsor, Tilley, Tyler, & Ormerod, ) and cycling between trophic levels, moving upwards through the food web as a consequence of predation (e.g. Nelms, Galloway, Godley, Jarvis, & Lindeque, ) and re‐entering the basal resources through egestion. The residence time of plastic particles within the biological component of food webs is unknown.…”
Section: Biological Retention and Cycling Of Plastics Across Catchmentsmentioning
confidence: 99%
“…However, experiments showing significant harm sometimes do so only with microplastic concentrations beyond what is common in the current environment (Cunningham & Sigwart, ; Lenz, Enders, & Gissel, ; Phuong et al, ). Trophic transfer of microplastics to higher levels of the food web, commonplace in marine systems (Carbery, Connor, & Thavamani, ; Nelms, Galloway, Godley, Jarvis, & Lindeque, ; Setälä, Fleming‐Lehtinen, & Lehtiniemi, ), has so far been only indirectly shown in terrestrial environments (Huerta Lwanga, Mendoza Vega, et al, ). If microplastics can be transferred from prey to predators in soil, it could result in microplastics escaping the confines of soil and spreading throughout the above‐ground food web, via the many terrestrial animals (including vertebrates) that consume soil invertebrates, but requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Trophic transfer of microplastics to higher levels of the food web, commonplace in marine systems (Carbery, Connor, & Thavamani, 2018;Nelms, Galloway, Godley, Jarvis, & Lindeque, 2018;Setälä, Fleming-Lehtinen, & Lehtiniemi, 2014), has so far been only indirectly shown in terrestrial environments (Huerta Lwanga, Mendoza F I G U R E 1 Diagram showing common microplastic shapes, six of the most common plastic polymers (Geyer, Jambeck, & Law, 2017), and sources and observed concentrations of microplastics in urban (1: Fuller and Gautam (2016)), riparian (2: Scheurer and Bigalke (2018)) and agricultural soils (3: Zhang and Liu (2018), 4: Piehl et al (2018), 5: Corradini et al (2019). Note that microplastic concentration in (5) Vega , et al, 2017).…”
mentioning
confidence: 99%